Cultural Represetation As Seen In Indonesian Early Bilinguals’ Essays - Zen, Evynurul L.; Rachmajanti, Sri; Apriana, Aulia (KnE Social Sciences, 2017)
A thorough observation on the implementation of immersion program at the Laboratory Primary School of Universitas Negeri Malang has recently been conducted particularly to see how English exposures work in non-English classrooms. The research also objectifies the initial mapping of the English proficiency of Early Bilinguals sitting in the 3rd Grade of International Class Program who are the main research subjects to whom the language proficiency tests are given. The findings indicate that the students possess good English language competence, comprehensively and productively. In language comprehension, 85% of the students are able to comprehend meanings of various explicit and implicit instructions in the forms of declaratives, interrogatives, and imperatives. In language production, 80% of the students are able produce simple and basic sytactic constructions (SVO order) accurately using almost correct singular-plural and present-past tense. Beyond these significant findings, the reseachers discover a lot more concern on how they construct ideas in their essays as well as how these ideas reflect their daily socio-cultural practices. Given the context of My Last Holiday, the 48-students’ essays have narrated more than only series of event or moments to remember, but a piece of universal concept internalized in their mind as Indonesian natives. This paper specifically outlines not only the most frequent words and phrases in their essays becoming apparent to represent the things the students value more, but also the initial mapping on universal cultural concepts in Asian context. Keywords: early bilinguals; essay writing, universal cultural concept